2010
DOI: 10.1007/s12325-010-0036-3
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of tapentadol prolonged release for chronic osteoarthritis pain and low back pain

Abstract: Tapentadol PR (100-250 mg twice daily) was efficacious and provided efficacy that was similar to oxycodone HCl CR (20-50 mg twice daily) for the management of chronic osteoarthritis knee and low back pain, with a superior gastrointestinal tolerability profile and fewer treatment discontinuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(181 citation statements)
references
References 18 publications
13
164
0
4
Order By: Relevance
“…Tapentadol has been shown to be effective and well tolerated for the management of moderate to severe, chronic pain in previous phase 3 studies [17−21], including randomized, doubleblind, placebo-controlled studies in patients with low back pain [18] and pain related to diabetic peripheral neuropathy [20]. A pooled analysis [19] were not a main objective of the trial, but were captured and are described here. Equianalgesic ratios were determined for tapentadol versus WHO step III analgesics, including analgesics other than oxycodone, which has been the primary active comparator during clinical trials evaluating tapentadol.…”
Section: Introductionmentioning
confidence: 99%
“…Tapentadol has been shown to be effective and well tolerated for the management of moderate to severe, chronic pain in previous phase 3 studies [17−21], including randomized, doubleblind, placebo-controlled studies in patients with low back pain [18] and pain related to diabetic peripheral neuropathy [20]. A pooled analysis [19] were not a main objective of the trial, but were captured and are described here. Equianalgesic ratios were determined for tapentadol versus WHO step III analgesics, including analgesics other than oxycodone, which has been the primary active comparator during clinical trials evaluating tapentadol.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine is associated with a higher incidence of GI side effects than many other opioids (Cook et al, 2008;Ishihara et al, 2012). Tapentadol, which is a μ opioid agonist that also inhibits norepinephrine reuptake, was as effective as oxycodone for managing chronic moderate to severe skeletal pain (Lange et al, 2010), but has fewer side effects (Stegmann et al, 2008). The incidence of constipation is lower for transdermal fentanyl than an equianalgesic dose of oral morphine (Tassinari et al, 2008).…”
Section: Optimisation Of Opioid Administrationmentioning
confidence: 99%
“…In-vitro radio ligand binding assays in rat brain membrane preparations have shown tapentadol to have only a modest affinity for the mu-opioid receptor relative to pure muopioid receptor agonists such as oxycodone ormorphine 19 , while in-vivo intra cerebral microdialysis studies in rats have shown that tapentadol, in contrast to morphine, produces large increases in extracellular levels of noradrenaline 20 . It has been suggested that the potential for lower reliance on mu-opioid receptor agonism to produce its analgesic effects, because of the contribution of the noradrenaline reuptake inhibition component, may account for the significantly lower level of opioid-associated side effects compared to equi-analgesic doses of oxycodone in clinical trials of tapentadol prolonged release 17 . Furthermore, because of the lack of significant clinical serotonergic activity with tapentadol, pain facilitation via the descending transmission system is not enhanced, and the side effects caused by increased serotonin in the CNS and the enteric nervous system are avoided 21 .…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…The very common adverse events reported were gastrointestinal and CNS events such as nausea, dizziness, constipation, headache and somnolence. However, tapentadol prolonged release demonstrates significant reductions in gastro intestinal side effects when compared with equianalgesic doses of oxycodone controlled release, associated with patients remaining on therapy for longer 17 .…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation